1998
DOI: 10.1002/(sici)1521-3765(19980210)4:2<251::aid-chem251>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Disubstituted [(6-Arene)Cr(CO)3] Complexes by Sequential Nucleophilic Addition/endo-Hydride Abstraction

Abstract: Regioselective addition of organolithium compounds at the ortho position in oxazoline, imine, or hydrazone (h 6 -arene)tricarbonyl chromium complexes afforded anionic [(h 5 -cyclohexadienyl)Cr(CO) 3 ] intermediates. A single-crystal Xray structure determination of the product of the addition reaction of naphthyllithium with a phenyl oxazoline complex showed structural characteristics of an aza-enolate superimposed on the predominant cyclohexadienyl structure. Reaction of the anionic cyclohexadienyl complex wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Moreover, excellent ortho-selectivity in Cr(CO) 3 complexed benzaldehyde imines has been demonstrated in both nucleophilic addition reactions and in lithiation reactions. 16,17,28,30 First data with complexes 8a and 8b are shown in Scheme 10 and Table 2. The imine complex 8a afforded product 34 in good yield but as a racemate (entry 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, excellent ortho-selectivity in Cr(CO) 3 complexed benzaldehyde imines has been demonstrated in both nucleophilic addition reactions and in lithiation reactions. 16,17,28,30 First data with complexes 8a and 8b are shown in Scheme 10 and Table 2. The imine complex 8a afforded product 34 in good yield but as a racemate (entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…(Scheme 2) [11][12][13] The methodology described here is an arene bound chiral auxiliary approach, with the auxiliary chosen to lead to diastereoselective ortho-addition to the complexed arene (1. in Scheme 2) 14,15 Aryl oxazoline (and also benzylidene cyclohexylamine) complexes have been shown previously to undergo selective ortho-additions of C-nucleophiles. While the intermediate anionic complex can be isolated and has been structurally characterized, 16 for the transformations with the electrophiles shown in Scheme 3 this is not required and in situ procedures have been used throughout. 17…”
Section: Biographical Sketchesmentioning
confidence: 99%
“…We note however that a related species has indeed been isolated from anionic (rather than zwitterionic) addition to Cr(CO) 3benzene. 25 This species also has an eclipsing interaction between one Cr-CO bond and the C-H bond at which nucleophilic addition has occurred.…”
Section: Palladium Insertion Intomentioning
confidence: 99%
“…2‐Lithio‐1,3‐dithiane reacts with (benzene)tricarbonylchromium [ 1 , M = Cr(CO) 3 ] to give an anionic η 5 ‐cyclohexadienyl complex 5a (Scheme ). This air‐sensitive intermediate can be observed spectroscopically and has been characterized by X‐ray diffraction analysis by Semmelhack et al8a Another study of a similar η 5 ‐structure ( 5b ) has recently been reported 8a. Oxidation of 5a at −78 °C with at least 2.5 mol‐equiv.…”
Section: General Reactivity Patterns Of (η6‐arene)tricarbonylchrmentioning
confidence: 94%